The integrated stress response is activated in the salivary glands of Sjögren’s syndrome patients - Carvajal, Patricia; Bahamondes, Verónica; Jara, Daniela; Castro, Isabel; Matus, Soledad; Aguilera, Sergio; Molina, Claudio; González, Sergio; Hermoso, Marcela; Barrera, María-José; González, María-Julieta (Frontiers in Medicine, 2023)
Introduction Primary Sjögren’s syndrome (SS) is an autoimmune exocrinopathy that affects the structure and function of salivary and lachrymal glands. Labial salivary gland (LSG) acinar cells from SS patients lose cellular homeostasis and experience endoplasmic reticulum and oxidative stress. The integrated cellular stress response (ISR) is an adaptive pathway essential for restoring homeostasis against various stress-inducing factors, including pro-inflammatory cytokines, and endoplasmic reticulum and oxidative stress. ISR activation leads eIF2α phosphorylation, which transiently blocks protein synthesis while allowing the ATF4 expression, which induces a gene expression program that seeks to optimize cellular recovery. PKR, HRI, GCN2, and PERK are the four sentinel stress kinases that control eIF2α phosphorylation. Dysregulation and chronic activation of ISR signaling have pathologic consequences associated with inflammation. Methods Here, we analyzed the activation of the ISR in LSGs of SS-patients and non-SS sicca controls, determining the mRNA, protein, and phosphorylated-protein levels of key ISR components, as well as the expression of some of ATF4 targets. Moreover, we performed a qualitative characterization of the distribution of ISR components in LSGs from both groups and evaluated if their levels correlate with clinical parameters. Results We observed that the four ISR sensors are expressed in LSGs of both groups. However, only PKR and PERK showed increased expression and/or activation in LSGs from SS-patients. eIF2α and p-eIF2α protein levels significantly increased in SS-patients; meanwhile components of the PP1c complex responsible for eIF2α dephosphorylation decreased. ATF4 mRNA levels were decreased in LSGs from SS-patients along with hypermethylation of the ATF4 promoter. Despite low mRNA levels, SS-patients showed increased levels of ATF4 protein and ATF4-target genes involved in the antioxidant response. The acinar cells of SS-patients showed increased staining intensity for PKR, p-PKR, p-PERK, p-eIF2α, ATF4, xCT, CHOP, and NRF2. Autoantibodies, focus score, and ESSDAI were correlated with p-PERK/PERK ratio and ATF4 protein levels. Discussion In summary, the results showed an increased ISR activation in LSGs of SS-patients. The increased protein levels of ATF4 and ATF4-target genes involved in the redox homeostasis could be part of a rescue response against the various stressful conditions to which the LSGs of SS-patients are subjected and promote cell survival.